Answer:
x = - 1, x = 8
Explanation:
Given
x² - 7x - 8 = 0 ( add 8 to both sides )
x² - 7x = 8
To complete the square
add ( half the coefficient of the x- term )² to both sides
x² + 2(-
)x +
= 8 +
=
![(81)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/kybfu7aymaf5whnvst7q3dv2zopkric55i.png)
(x -
)² =
( take the square root of both sides )
x -
= ±
= ±
( add
to both sides )
x =
±
![(9)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7t74ao2ijtpnvsdut79yo96cyp20lcu8uj.png)
Thus
x =
-
=
= - 1
x =
+
=
= 8